2015
DOI: 10.3390/ijms160614086
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-Derived Growth Factor: Its Possible Involvement in the Progression of Hepatocellular Carcinoma

Abstract: The development of hepatocellular carcinoma (HCC) is an important complication of viral infection induced by hepatitis virus C, and our major research theme is to identify a new growth factor related to the progression of HCC. HDGF (hepatoma-derived growth factor) is a novel growth factor that belongs to a new gene family. HDGF was initially purified from the conditioned medium of a hepatoma cell line. HDGF promotes cellular proliferation as a DNA binding nuclear factor and a secreted protein acting via a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…To investigate the target gene of the LINC00958/ miR-3619-5p pathway in HCC, we combined four bioinformatics algorithms and RNA sequencing results and found that HDGF was the downstream effector of the LINC00958/miR-3619-5p axis. HDGF has been established as an oncogene that facilitates the progression of HCC [40,41]. One recent study suggested that HDGF could affect lipid metabolism via SREBP1 in HCC [25].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the target gene of the LINC00958/ miR-3619-5p pathway in HCC, we combined four bioinformatics algorithms and RNA sequencing results and found that HDGF was the downstream effector of the LINC00958/miR-3619-5p axis. HDGF has been established as an oncogene that facilitates the progression of HCC [40,41]. One recent study suggested that HDGF could affect lipid metabolism via SREBP1 in HCC [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoma-derived growth factor (HDGF) is a secreted multifunctional protein that is highly expressed in pulmonary endothelial cells as an angiogenic factor (13)(14)(15)(16)(17). It is also involved in lung remodeling by stimulating bronchial and alveolar epithelial cell growth (18).…”
mentioning
confidence: 99%
“…Hepatoma-derived growth factor (HDGF) is detectable in the conditioned medium of the human hepatoma Huh7 cell line (Nakamura, Izumoto et al, 1994) and has been suggested to play a pro-tumor role in the promotion of hepatoma cell proliferation (Enomoto, Nakamura et al, 2015, Kishima, Yamamoto et al, 2002, metastasis (Yamamoto, Tomita et al, 2006), invasion, epithelial-mesenchymal transition (Chen, Kung et al, 2012), and angiogenesis (Shih, Tien et al, 2012). The divergent HDGF functions participate in a broad range of cancer cell activities.…”
Section: Introductionmentioning
confidence: 99%